Kritik Ideologi terhadap Nilai Sosial Budaya Pernikahan dalam Novel Di bawah Bayang-Bayang Ode - Suriadin P Suriadin P; Apsanti Djokosujatno (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2021)
This study aims 1. To gain an in-depth understanding of the intrinsic elements contained in Sumiman Udu's novel Di Bawah Bayang-Bayang Ode. 2. To gain an in-depth understanding of the extrinsic elements contained in Sumiman Udu's novel Di Bawah Bayang-Bayang Ode. 3. To gain an in-depth understanding of the social and cultural values of marriage in Sumiman Udu's novel Di Bawah Bayang-Bayang Ode. 4. To gain an in-depth understanding of the ideological critique of the socio-cultural values of marriage in Sumiman Udu's novel Di Bawah Bayang-Bayang Ode. The method used in this research is qualitative research using a genetic structuralism approach. The ideological criticism in the novel “Di Bawah Bayang-Ode” is a rejection of the belief of the Ode clan community that requires marriage to other clans so that parents are forced to marry their children to other clans. This is not only a form of discrimination against social classes that do not have an Ode clan, but also does not reflect the morals of an Ode clan. Besides that, the existence of the title "Ode" in the Butonese people is still very much appreciated, so that the marriage is done forcibly. Problems that occur next, when living the behavior of the household. Feelings of dislike (hate) are still lingering in the minds of the family, on the basis that they are not only entitled "Ode". Keyword: Ideological Criticism, Socio-Cultural Values of Marriage, Under the Shadow of Ode